Revitalising the Role of Literature in the Contemporary EFL Secondary Classroom: A Small-scale Study - Romo-Mayor, Paula; Pellicer-Ortín, Silvia (Didáctica. Lengua y Literatura, 2022)
It can be asserted that nowadays a vast proportion of the world’s population needs to develop communicative competence in English to participate in transnational societies. Although there is still some reticence to use literature in the English as a Foreign Language (EFL) context, our main claim is that literary resources may be a powerful tool for the development of intercultural communicative competence in English. In particular, the main purpose of this article is to examine the extent to which literary resources are used in EFL teaching and analyse which literary genres are more attractive and appropriate for teenagers. In this study we have observed the extent to which literature is currently used in the teaching of EFL in the stage of secondary education in the region of Aragón. For that, the method to follow has been based on the development of different surveys used to gather information about the popularity of literature in some Aragonese classrooms. In addition to this, the literary genres which are more appropriate for teenagers have been examined through the creation of a checklist, and these data have supported the design, creation and partial implementation of an innovative project in the secondary-education classroom. The results of this implementation have led us to demonstrate that the development of communicative competence in our younger generations can be enhanced through literary texts if the selection and methodology used in the classroom are adequate.